Analysis of the pragmatic competence profile in the population with 22q11.2 syndrome: a comparison between syndromic presentations - Moraleda Sepulveda, Esther; Loro Vicente, Nadia; Durán-Heras, Patricia; Chaves-Herráiz, Patricia (Frontiers in Education, 2025)
IntroductionVarious studies confirm that individuals with 22q11.2 syndrome exhibit communicative alterations that affect their social interactions. However, few compare the pragmatic characteristics of these individuals based on the type of syndrome (either deletion or duplication).MethodThis research aims to address the pragmatic skills of 10 participants with 22q11.2 syndrome, comparing the types 22q11.2DupS and 22q11.2DS, within an age range of 7 to 17 years, thereby confirming or denying communicative differences between syndromic presentations. The evaluation was conducted using the Revised Quick Pragmatic Assessment Protocol, allowing observation of the communicative characteristics of participants at the textual, utterance, and interactive levels. Video recordings of conversational samples with close interlocutors were used for the evaluation.ResultsThe results show that, in general, there are differences between the two types of the syndrome, with more pragmatic difficulties in the case of people 22q11.2DS.ConclusionThese differences do not appear to be related to age, as the percentage of different items is similar across both age ranges. Some limitations of the study are discussed.